DISTRIBUTED VISUAL PATTERN STRUCTURE FEATURES BY “X-RAYING” OF INTENSITY - Melnyk, Roman; Kalychak, Yuriy (International Journal of Computing, 2010)
An approach to determine structural integral and distributed image features on the basis of the “X-ray” algorithm from the perspective of the frontal plane XOZ or lateral plane YOZ is considered. The distributed structural features of segments are formed for the space of intensity. Segmentation is performed through splitting the image and space by intensity and coordinate values. The results of defined features and searching algorithm are presented.